2007
DOI: 10.1111/j.1745-4514.2007.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Microbial Changes During the Natural Fermentation of Strawberry Tree (Arbutus Unedo L.) Fruits

Abstract: Aguardente de medronho is the name given in Portugal to a spirit made from the fermented fruit of Arbutus unedo (strawberry tree), a plant grown in the Mediterranean region. In order to gain a better understanding of the fermentation process, as it is performed in the farms, a natural fermentation with wild microbiota was carried out during 36 days, and some physicochemical and microbiological parameters were studied. The microbial parameters analyzed were total viable, lactic and acetic acids bacteria, and ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 14 publications
5
20
0
Order By: Relevance
“…The low pH and the high concentration of sugars (°Brix 15) at the beginning of the fermentations favored the multiplication of the yeast biota. According to previously published results, the berries of A. unedo are characterized by low pH values and high soluble sugar concentrations reaching more than 20 g/l as described by Cavaco et al (2007).…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…The low pH and the high concentration of sugars (°Brix 15) at the beginning of the fermentations favored the multiplication of the yeast biota. According to previously published results, the berries of A. unedo are characterized by low pH values and high soluble sugar concentrations reaching more than 20 g/l as described by Cavaco et al (2007).…”
Section: Resultsmentioning
confidence: 79%
“…The berries are also an interesting source of omega-3 polyunsaturated fatty acids (Oliveira et al, 2011). However, the fruits' main application is the production of a distilled beverage known as "Aguardente de medronho" in Portugal (Cavaco, Longuinho, Quintas, & Carvalho, 2007), "Koumaro" in Greece (Soufleros et al, 2005) and "Corbezzolo" in Italy (Versini et al, 1995). This beverage is a traditional product made in small or industrial scale units during the months of September to January and its production constitutes a agro-sustainable business which makes A. unedo an interesting shrub by social and economic reasons (Alarcão-E-Silva, Leitão, Azinheira, & Leitão, 2001;González, Agrasar, Castro, Fernández, & Guerra, 2011;Soufleros et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, these fruits have been used to treat arterial hypertension (Cavaco, Longuinho, Quintas, & Saraiva 2007) or as antiseptics, diuretics and laxatives in traditional folk medicine (Ayaz, Kucukislamoglu, & Reunanen 2000;Pabuçcuoglu, Kivçak, Bas, & Mert 2003). In the same way, raspberries (Rubus idaeus L.) have reported to contain high levels of ellagic acid (Juranic et al, 2005), which has shown to have antiviral activity (Corthout, Peiters, Claeys, Vanden Berghe, & Vleitinck 1991) and anticancer potential (Stoner & Morse 1997).…”
Section: Introductionmentioning
confidence: 99%